Biological inspired flying robot - Couceiro, Micael S. (2009)
This paper presents the development of computational simulation based on the dynamics of a robotic bird. The study analyze the wing angle of attack and the velocity of the bird, the tail influence, the gliding flight and the flapping flight with different strategies and algorithms of control. The results are positive for the construction of flying robots. Some highlights are given about the fist implemented architecture of the structure of a robotic bird. This platform consists on a body, wings and tail with actuators independently controlled though a microcontroller; a radio transmission system and batteries are used in order to avoid wired connections between the computer and the robot.